Identifikasi Situs-Situs Peninggalan Belanda di Kota Tua Abepura - Loppies, Megiridha; Hasirun, La Ode; Kulyasin; Wetipo, Meki (J-Abdimas Cenderawasih, 2024)
This community service aims to identify buildings and historical sites left by the Dutch government (Nederlands Nieuw Guinea) in the old city of Abepura so that the historical heritage of Abepura City's past can be preserved for future generations. The methods used in this service are (1) Field survey, conducting surveys in the field to find potential locations that are suspected to be Dutch heritage sites in Abepura; (2) Documentation: Documenting the sites discovered through collecting information and photographs; (3) Identification and reflection: Identifying the sites discovered by comparing them with historical data and information regarding Dutch heritage in the Abepura area; (5) Reporting: report the results of identifying historical sites in Abepura in the form of a written report which will be submitted to the Jayapura City Culture and Tourism Office. The results of the service found several identified Dutch heritage buildings, namely the Harapan Abepura church building, half-round houses, houses that used to live by Dutch employees, former administrative office buildings (transistors), the GKI I. S. Kijne Theological College (STT) building and housing of Lecturer at the STT complex. These buildings need to be designated as historical sites so that the history of Abepura City is maintained and preserved for future generations.